Motor improvement of remote programming in patients with Parkinson's disease after deep brain stimulation: a 1-year follow-up - Wan, Xiaonan; Duan, Chengcheng; Lin, Zhengyu; Zeng, Zhitong; Zhang, Chencheng; Li, Dianyou (Frontiers in Neurology, 2024)
Background Remote programming (RP) is an emerging technology that enables the adjustment of implantable pulse generators (IPGs) via the Internet for people with Parkinson's disease (PwPD) who have undergone deep brain stimulation (DBS). Previous studies have not comprehensively explored the effectiveness of RP in managing motor symptoms, often omitting assessments such as the rigidity and retropulsion tests during the follow-up. This study evaluates the comprehensive improvements in motor performance and the potential cost benefits of RP for PwPD with DBS. Methods A retrospective analysis was conducted on two groups of patients—those who received RP and those who received standard programming (SP). Clinical outcomes including motor improvement, quality of life, and daily levodopa dosage were compared between the groups during a 12 (± 3)-month in-clinic follow-up. Results A total of 44 patients were included in the study, with 18 in the RP group and 26 in the SP group. No significant differences were observed in the frequency of programming sessions or clinical outcomes between the groups (p > 0.05). However, the RP group experienced significantly lower costs per programming session than the SP group (p < 0.05), despite patients in the former group living further from our center (p < 0.05). Conclusions Our findings suggest that RP could significantly reduce the costs of programming for PwPD with DBS, especially without compromising the effectiveness of treatment across all motor symptoms in the short term.